Complex Interactions between Temperature and Relative Humidity on Water Balance of Adult Tsetse (Glossinidae, Diptera): Implications for Climate Change - Kleynhans, Elsje; Terblanche, John S. (Frontiers in Physiology, 2011)
Insect water balance plays an important role in determining energy budgets, activity patterns, survival and population dynamics and, hence, geographic distribution. Tsetse (Glossina spp.) are important vectors of human and animal disease occupying a wide range of habitats in Africa and are notable for their desiccation resistance in xeric environments. Here, we measure water balance traits (water loss rate, body water content and body lipid content) in adult flies across a range of temperature (20 – 30 °C) and relative humidity (0 – 99 %) combinations in four tsetse species from both xeric and mesic habitats. Water loss rates were significantly affected by measurement under different temperature and relative humidity combinations, while body water content, body lipid content and mass were less affected. Different effects of temperature and relative humidity within and among experimental conditions and species suggests cuticular permeability and saturation deficit are likely to be key factors in forecasting tsetse water balance responses to climate variability. These results provide support for mass–independent inter– and intra–specific variation in water loss rates and survival times. Therefore, water balance responses to variation in temperature and relative humidity are complex in Glossina, and this response varies within and among species, sub–groups and ecotypes in terms of both magnitude of effects and the direction of change. This complicates potential forecasting of tsetse distribution in the face of climate change.